Successful practice in neuropsychology and neuro-rehabilitation : a scientist-practitioner model - Pepping, Mary (Practical resources for the mental health professional., 2014)
This 2nd edition (of the original Successful Private Practice in Neuropsychology) provides an updated overview of key principles and processes for establishing, maintaining and developing neuropsychology practice and neuro-rehabilitation program (NRP) treatment in medical center and/or private practice settings. Essential elements of an entrepreneurial model that work well in the medical center context and the necessary role of variety and peer review in the private practice setting are also discussed. How to gather and report NPE and other evaluation findings with a neuro- rehabilitation foc.